THE PROBLEMS OF INHERITANCE DISTRIBUTION BEFORE DEATH - Abdul Hakim; Ali Alkosibati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article discusses the inheritance distribution before death which is the preference of many people in Babat, East Java. They thought this distribution could prevent dispute among the heirs after the death of the predecessor. However, the dispute is unavoidable. This distribution is also problematic from the perspective of the four madhhabs. This is a qualitative and library research using the case study approach. This study shows that the inheritance distribution before death in the Babat area generally uses hibah method; only some apply the wasiat method. Although the inheritance distribution before death is problematic from the perspective of the four madhhabs in some cases, this is the choice of the Babat community because they consider this method to be more effective in preventing disputes. The inheritance distribution before death also plays an important role in minimizing family disputes in the area, especially if hibah and wasiat are practiced according to Islamic law and issues related to hibah are completely resolved to avoid disputes and struggles for rights in the future. يناقش هذا البحث عملية تقسيم الميراث قبل الوفاة التي صارت اختيار كثيرٍ من الناس في منطقة بابات. إنهم يعتبرون هذا التقسيم أحسن طريقة لدفع النزاعات في الأسرة بعد وفاة المورّث. لكن في الواقع، لا تسلم هذه الطريقة من النزاعات. ومن تلك النزاعات ما أدى إلى طرد زوج المورثة من المنزل. وبالإضافة إلى ذلك، فإن تقسيم الميراث قبل الوفاة في منطقة بابات يتضمن مشكلات فقهية من وجهة نظر المذاهب الأربعة، لا سيما عند ممارسة عقد الهبة أو الوصية. هذا البحث هو البحث النوعي الميداني والمكتبي باستخدام منهج دراسة الحالة. توصل هذا البحث إلى أن تقسيم الميراث قبل الوفاة في منطقة بابات تم على طريقة الهبة في الغالب، وقد يتم التقسيم أيضا على طريقة الوصية، لكنه نادر. وإن كان تقسيم الميراث قبل الوفاة يتضمن مشكلات من وجهة نظر المذاهب الأربعة في بعض الحالات، إلا أنه صار اختيار المجتمع في بابات؛ لأنهم يعتبرون أن هذا التقسيم أكثر فعالية في منع النزاع. ويلعب تقسيم الميراث قبل الوفاة أيضًا دورًا مهمًا في تقليل النزاعات الأسرية في منطقة بابات، خاصة إذا كانت الهبات والوصايا تمت على وفق ما قُرّر في الشريعة الإسلامية وتم حل القضايا المتعلقة بالموهوب مثل تسجيل شهادات الأراضي وغيره لتجنب النزاعات والتناضل من أجل الحقوق في المستقبل.